Advancing thermal performance in PCM-Based energy Storage: A comparative study with Fins, expanded Graphite, and combined configurations - Ajay Muraleedharan Nair; Christopher Wilson; Babak Kamkari; Jake Locke; Ming Jun Huang; Philip Griffiths; Neil J Hewitt (Energy Conversion and Management: X, 2024)
Phase Change Material (PCM) thermal energy storage systems have emerged as a promising solution for efficient thermal energy storage from low to very high-temperature applications. This paper presents an investigation into the utilization of medium temperature range PCM-based systems for domestic hot water application, focusing on different techniques to overcome the low thermal conductivity of the PCM. Five shell and tube heat exchangers were fabricated employing different heat transfer enhancement methods including fin, expanded graphite (EG), and a combination of fin and EG. The combination of EG and circular fins exhibited the best performance in terms of charging and discharging, maintaining a uniform temperature distribution throughout the system due to extensive conductive network provided by the combination of EG and circular fins. When the PCM/EG/fin heat exchanger system is fully charged, the energy stored in the system is 109% higher than that of the PCM heat exchanger at the same elapsed time. Furthermore, the PCM/EG/fin system demonstrated a faster discharging response compared to other thermal energy storage (TES) configurations, with over 160% higher discharging power than a system without any enhancement methods. These findings emphasize the practical viability of integrating PCM/EG composite materials into thermal energy storage systems, offering a viable solution for meeting high heat demand requirements in domestic hot water applications. Furthermore, the enhanced discharging response observed in the PCM/EG/fin system has significant implications for improving energy efficiency and reducing operational costs in real-world applications.